President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2021)
The theme of this year's ORNAC National Conference is “Charting the future of Perioperative Practice” and, in 2021, this theme could not be more appropriate. Since March of last year Canadian perioperative nurses have been facing many challenges, due to the impact of COVID-19, that require much strength, courage and flexibility. They have certainly risen to this challenge and charted their way into a new world. Perioperative Registered Nurses respond to complex and changing clinical needs during a crucial period of a person's surgical experience. The scope of perioperative nursing practice is continually evolving as RNs respond to societal, technological, and economic changes.